Nasal High Frequency Oscillatory Ventilation for Respiratory Failure due to Respiratory Syncytial Virus Bronchiolitis: Case Report - Liberatore, Pio (AJP Rep, 2020)
The authors describe a case of acute respiratory failure due to severe bronchiolitis. During high-flow nasal cannula ventilation, the blood's high levels of hypercapnia had taken them to plan the sedation and the orotracheal intubation. However, before attempting intubation, a nasal high frequency oscillatory ventilation cycle was performed and it led to a marked improvement in the blood gas, avoiding in this way the invasive ventilation.